2003
DOI: 10.11646/zootaxa.309.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Crossota millsae (Cnidaria: Trachymedusae: Rhopalonematidae), a new species of viviparous hydromedusa from the deep sea off California and Hawaii

Abstract: A new species of deep-sea jellyfish, Crossota millsae (Cnidaria: Hydrozoa: Trachymedusae: Rhopalonematidae), is described from the North Pacific Ocean off California and Hawaii. Discrete depth sampling showed this species lives at depths below 1000 meters in both geographic locations. The species is more abundant off California than off Hawaii. The greatest population densities were found at~2500 m off California and at~1250 m off Hawaii. The burnt-tangerine color of the inner bell and bright pink to lavender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…A large literature indicates that cnidarians are no exception to this phenomenon and are indeed renowned for exhibiting high levels of developmental phenotypic plasticity (e.g. Hincks 1868, Merejkowsky 1883, Van Beneden 1884, Schmid 1974, Bavestrello et al 1992, Boero et al 1996, Bavestrello et al 2000, Schroth et al 2002, Thuesen 2003. The extent to which scyphozoans exhibit phenotypic morphological variation in response to new environmental conditions is, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A large literature indicates that cnidarians are no exception to this phenomenon and are indeed renowned for exhibiting high levels of developmental phenotypic plasticity (e.g. Hincks 1868, Merejkowsky 1883, Van Beneden 1884, Schmid 1974, Bavestrello et al 1992, Boero et al 1996, Bavestrello et al 2000, Schroth et al 2002, Thuesen 2003. The extent to which scyphozoans exhibit phenotypic morphological variation in response to new environmental conditions is, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…10, 3,668 m depth, 14:21, 8 Jun 2000, off Hawai'i, California (2,540 m and 3,244 m depth) and in the Sea of Cortez (Thuesen 2003), as well as from depths between 1,614 and 2,093 m in the Chukchi Basin, Arctic Ocean . During the present study it was observed at 1,440 m depth during ROV HyperDolphin dive 296. perradial manubrial pouches, oval in outline, usually somewhat longer than wide, septa between them alternating with tentacle roots; 20-40 marginal tentacles, stiff, tapering, up to slightly longer than diameter of umbrella; no peripheral canal system; gonads?…”
Section: Macroplanktonic Predators Considered Capable Of Preying On Vmentioning
confidence: 97%
“…On this occasion, the animal travelled three body lengths. The size of the animal was not recorded but the species has been described as being up to 28 mm wide ( Thuesen, 2003 ). Its orientation was such that changes in bell height and diameter could be measured sufficiently accurately to reveal a significant delay in the onset of contraction in the mid-bell region.…”
Section: Resultsmentioning
confidence: 99%